Tensile strength and cellulose content of Persian ironwood (Parrotia persica) roots as bioengineering material - E. Abdi; F. Azhdari; A. Abdulkhani; H. Soofi Mariv (Journal of Forest Science, 2014)
Unstable slopes create numerous problems for forest management and may destroy the road network and disturb access to forest. Soil bioengineering is a solution that can prevent these problems and reinforce the hillslope. Persian ironwood is considered as a good protective species for hillslope stability in Iran with an extensive lack of information about biotechnical properties. In this research the root strength of this species and also the relation between root diameter and cellulose content were investigated. The results showed that the mean tensile force and tensile strength were 99.70 ± 2.01 N and 173.23 ± 4.94 MPa, respectively, for the root diameter range between 0.22 and 3.78 mm. The results of ANOVA showed that the power models between root diameter and tensile force and tensile strength were statistically significant and the results of t-test showed that coefficients and constants of the models are also significant. The values of the parameters of the power law (α and β) obtained for Persian ironwood do not fall in the range that has already been suggested for hardwood roots, which may be due to a narrow diameter range. The mean cellulose content was 56.87 ± 5.79% and the relationship between root diameter and cellulose content was not statistically significant. The data presented in this study expand the knowledge of biotechnical properties of Persian ironwood and support the idea that there is still an extensive lack of information about plant roots as a bioengineering material.